Nāgarakṛtâgama political philosophy and its relevance to Indonesian defense diplomacy today - Ni Nyoman Ayu Nikki Avalokitesvari; I Wayan Titra Gunawijaya (Institute for Advanced Science, Social, and Sustainable Future, 2023)
History proves that the ancient regions known as the Archipelago already had an advanced government system. Arthaśāstra's knowledge of governance is reflected in the royal arrangements, defense systems, and patterns of international diplomacy that are applied. One of the knowledge of the ancient government is contained in Nāgarakṛtâgama, which describes the concept of the mandala of the Majapahit kingdom. Two political texts on Javanese land, namely Kakawin Nitisastra, and Nāgarakṛtâgama, have close links with Hindu politics, which are listed in various literature such as the Rāmāyaṇa, Māhābharata, and the treatise on politics and government of Arthaśāstra. This article is the result of research on the Nāgarakṛtâgama text and its context on the Indonesian defense diplomacy system. Data were obtained through literature studies, interviews, and FGDs with defense policymakers. The theory used is the interpretation of Paul Ricoeur with data analysis using Ethnographic Content Analysis (ECA). Majapahit, built with the breath of the Hindu-Buddhist religion, wanted to establish the sacred tradition of the kingdom in order to develop people's welfare. The political constellations are known as mandalas which depict political maps, military constellations, and diplomacy. Mitreka state is a well-known Majapahit diplomacy jargon listed in chapter 15. Majapahit places several kingdoms as equal kingdoms or friendly countries, in addition to a number of countries with good relations or enemies that can invade at any time. The Majapahit political map is essential to understand to build geopolitical awareness and efforts to rebuild political learning for youth in the country. Besides that, Nāgarakṛtâgama's political philosophy is powerfully relevant to the current state defense diplomacy system.